A Heroin Addiction Severity-Associated Intronic Single Nucleotide Polymorphism Modulates Alternative Pre-mRNA Splicing of the μ Opioid Receptor Gene OPRM1 via hnRNPH Interactions - Xu, Jin (Society for Neuroscience, 2014)
Single nucleotide polymorphisms (SNPs) in the OPRM1 gene have been associated with vulnerability to opioid dependence. The current study identifies an association of an intronic SNP (rs9479757) with the severity of heroin addiction among Han-Chinese male heroin addicts. Individual SNP analysis and haplotype-based analysis with additional SNPs in the OPRM1 locus showed that mild heroin addiction was associated with the AG genotype, whereas severe heroin addiction was associated with the GG genotype. In vitro studies such as electrophoretic mobility shift assay, minigene, siRNA, and antisense morpholino oligonucleotide studies have identified heterogeneous nuclear ribonucleoprotein H (hnRNPH) as the major binding partner for the G-containing SNP site. The G-to-A transition weakens hnRNPH binding and facilitates exon 2 skipping, leading to altered expressions of OPRM1 splice-variant mRNAs and hMOR-1 proteins. Similar changes in splicing and hMOR-1 proteins were observed in human postmortem prefrontal cortex with the AG genotype of this SNP when compared with the GG genotype. Interestingly, the altered splicing led to an increase in hMOR-1 protein levels despite decreased hMOR-1 mRNA levels, which is likely contributed by a concurrent increase in single transmembrane domain variants that have a chaperone-like function on MOR-1 protein stability. Our studies delineate the role of this SNP as a modifier of OPRM1 alternative splicing via hnRNPH interactions, and suggest a functional link between an SNP-containing splicing modifier and the severity of heroin addiction.